2002
DOI: 10.4049/jimmunol.168.7.3412
|View full text |Cite
|
Sign up to set email alerts
|

Increased Survival in Sepsis by In Vivo Adenovirus-Induced Expression of IL-10 in Dendritic Cells

Abstract: The dendritic cell (DC) is the most potent APC of the immune system, capable of stimulating naive T cells to proliferate and differentiate into effector T cells. Recombinant adenovirus (Adv) readily transduces DCs in vitro allowing directed delivery of transgenes that modify DC function and immune responses. In this study we demonstrate that footpad injection of a recombinant Adv readily targets transduction of myeloid and lymphoid DCs in the draining popliteal lymph node, but not in other lymphoid organs. Pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
44
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 36 publications
3
44
0
3
Order By: Relevance
“…In two previous reports, we observed that the in vivo transfection of DCs with an adenoviral recombinant expressing IL-10 generated a regulatory-like DC population that protected mice from CLP-induced mortality (17,23). Interestingly, similar improvements in outcome could be obtained when the animals received adoptive transfer of DCs transduced ex vivo to produce IL-10 (26).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In two previous reports, we observed that the in vivo transfection of DCs with an adenoviral recombinant expressing IL-10 generated a regulatory-like DC population that protected mice from CLP-induced mortality (17,23). Interestingly, similar improvements in outcome could be obtained when the animals received adoptive transfer of DCs transduced ex vivo to produce IL-10 (26).…”
Section: Discussionmentioning
confidence: 63%
“…For induction of polymicrobial sepsis, mice (n ϭ 11 per treatment group) were subjected to CLP as previously described (16,17). In brief, laparotomy was performed, and the cecum was isolated, ligated, and punctured through and through with a 22-gauge needle.…”
Section: Cecal Ligation and Puncturementioning
confidence: 99%
“…First, one injection of Ad-shNUCB2 may not be enough for significantly knocking down central nesfatin-1/NUCB2. Because adenovirus-mediated gene expression was considered to be dose and time dependent in a linear fashion (23,24), multiple injections to increase vector dose may be required for a large effect on gene expression and, consequently, on the food intake. Second, there was insufficient blockade (50%) of NUCB2 translation at key hypothalamic nuclei related to food intake.…”
Section: Discussionmentioning
confidence: 99%
“…For induction of polymicrobial sepsis, mice were subjected to a CLP as described previously (21,22). In brief, a laparotomy was performed, and the cecum was isolated, ligated below the ileocecal valve, and punctured through and through with a 23-gauge needle.…”
Section: Cecal Ligation and Puncturementioning
confidence: 99%